If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-21=-4w+7(w-6)
We move all terms to the left:
-21-(-4w+7(w-6))=0
We calculate terms in parentheses: -(-4w+7(w-6)), so:We get rid of parentheses
-4w+7(w-6)
We multiply parentheses
-4w+7w-42
We add all the numbers together, and all the variables
3w-42
Back to the equation:
-(3w-42)
-3w+42-21=0
We add all the numbers together, and all the variables
-3w+21=0
We move all terms containing w to the left, all other terms to the right
-3w=-21
w=-21/-3
w=+7
| 37=2y+5(y+6) | | 32=2v+2(v-4) | | -6u+4(u+3)=16 | | 36=5x+2(x-3) | | -6x+-3+7=-5 | | (80-x)=2/3 | | 12x4x=24 | | -3(2m+1)=7=-5 | | 260-y=158 | | 8x+114=210 | | -x+5=199 | | 2x-4x=36 | | 9^-4r=58 | | 2^n-^8=89 | | (x-12)+2x+48+x=180 | | 2^n-8=89 | | 3x+3+5x-1=180 | | 9*13^x=3 | | 9x13^x=3 | | (3x=23) | | 10^m-2=-38 | | E^n=16 | | 2z+20-3z=1.5(6z+4 | | 6/5x-3/2-9/10x=3/(x-5) | | 16y2=-13y | | 9^x=59 | | -4a^2-33a=-8 | | 1.5x=1.60 | | 0=8n-8n | | 3w-6=6w | | 11v+18=14v | | 12(-s+2)+17s=-6 |